Case-based reasoning research and development : 25th International Conference, ICCBR 2017, Trondheim, Norway, June 26-28, 2017, Proceedings /: 25th International Conference, ICCBR 2017, Trondheim, Norway, June 26-28, 2017, Proceedings. (2017) - Unknown
No abstract available